2021
DOI: 10.1155/2021/9307474
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Writing Self-Assessment and Peer Assessment on Iranian EFL Learners’ Autonomy and Metacognitive Awareness

Abstract: One of the most significant current discussions in writing is self-assessment and peer assessment. This study aimed to investigate the impact of writing self-assessment and peer assessment on autonomy and metacognitive awareness of Iranian EFL learners. One hundred and twenty participants were selected using convenience sampling. Four instruments were used in this test: (1) Nelson placement test; (2) Metacognitive Awareness Inventory (MAI); (3) Zhang and Li’s autonomy questionnaire; and (4) rubric. A quasiexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In general, peer assessment is a test given to students and then corrected by friends with predetermined guidelines (Mellinger, 2019;Zheng et al, 2017). In addition, peer assessment is also considered an alternative assessment procedure and has been recognized as an activity used by learners to assess each other's performance (Ebrahimi et al, 2021). The use of an eportfolio improves students' development of metacognitive ability especially in implementing as well as evaluating (Gutiérrez-Santiuste et al, 2022;Händel et al, 2020;Karami et al, 2019;López-Crespo et al, 2022;Lukitasari et al, 2021;Segaran & Hasim, 2021;.…”
Section: Implementing Of Assessment As Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, peer assessment is a test given to students and then corrected by friends with predetermined guidelines (Mellinger, 2019;Zheng et al, 2017). In addition, peer assessment is also considered an alternative assessment procedure and has been recognized as an activity used by learners to assess each other's performance (Ebrahimi et al, 2021). The use of an eportfolio improves students' development of metacognitive ability especially in implementing as well as evaluating (Gutiérrez-Santiuste et al, 2022;Händel et al, 2020;Karami et al, 2019;López-Crespo et al, 2022;Lukitasari et al, 2021;Segaran & Hasim, 2021;.…”
Section: Implementing Of Assessment As Learningmentioning
confidence: 99%
“…Self-assessment can increase students' metacognitive awareness (Ebrahimi et al, 2021). On the other hand, self-assessment is a reflection tool (Siegesmund, 2017).…”
Section: The Effect Of Implementing Assessment As Learning On Student...mentioning
confidence: 99%
See 1 more Smart Citation
“…Students have the chance to learn collaboratively through peer assessment by really supporting one another and sharing their experiences [16]. It enhances academic achievement [17], [18], EFL students' independence and understanding of their own metacognition when completing writing assignments [19]. Peer assessment has the potential to effectively address the issue of the teacher-student ratio in Chinese higher education while also fostering the growth of a variety of learner abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, Herwiana (2021) showed that peer feedback can help learners improve their grammar and vocabulary. Regarding motivational effects, Vahid and Hossein (2016) provided empirical evidence that peer feedback played a critical role in increasing students' academic motivation. Additionally, Liang (2006) asserted that a fair, supportive, and welcoming assessment environment can help students better understand learning objectives.…”
Section: Introductionmentioning
confidence: 99%